PELATIHAN KADER KESEHATAN GIGI DAN MULUT DI DESA KARYAMEKAR KEC.CILAWU DALAM MENCEGAH TERJADINYA STUNTING - Chaerudin, Denden Ridwan; Heriyanto, Yonan; Widyastuti, Tri; Praptiwi, Yenni Hendriani; Rizqi, M. Aris (Poltekkes Kemenkes Bandung, 2024)
Stunting is a nutritional problem caused by a lack of nutritional intake from food that lasts long enough. Good and proper nutrition is important to support dental health. Conversely, dental health is also important for adequate nutritional intake. The severity of dental caries is a risk of lack of nutritional intake. The stunting rate of Garut Regency is currently at 23%, while the national average is 21%. According to the performance report of Bojongloa Health Center in December 2022 there were 82 toddlers with stunting cases, and there were 38 toddlers with malnutrition status. The purpose of this community service is to help the community, especially cadres and pregnant women, in increasing knowledge about oral health through the regional partnership program. The cadres involved totaled 22 people, who were representatives from each RW 01 - 11 of 10 posyandu. The results before training showed the average value obtained by cadres was 3.5 and 7.5 average value obtained after training. At the time of cadre assistance, the average value obtained before counseling on pregnant women was 4.4, and after counseling an average value of 6.8 was obtained. While the results of the assessment of cadre skills in counseling are in the moderate category. Conclusion: there is an increase in cadre knowledge about dental health and balanced nutrition with moderate kreteria (72%), and the results of the evaluation of cadre skills in counseling pregnant women with sufficient kreteria.